MENINGKATKAN KEMAMPUAN PENGENALAN KONSEP WARNA MELALUI STRATEGI BERMAIN KARTU DOMINO WARNA PADA ANAK USIA 4-5 TAHUN DI KB BUNGA TERATAI KECAMATAN TAPUNG KABUPATEN KAMPAR - Ernawati, Lili; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to improve the introduction of color, learn strategies to play dominoes, and the high increase in the ability of the introduction of color in early childhood age 4-5 years at KB Bunga Teratai Tapung Kampar district. The research methodology used in this study is classroom action research study was conducted in KB Bunga Teratai Tapung Kampar district with a planned study in accordance with a predetermined time. The increase continued. From the data before the treatment can be an average value sebesar36,53% increase in the first cycle to 43.97%. From the data in the data before the treatment cycle an increase of 20.3%. And in the second cycle the average value obtained by 71.15% compared with the first cycle with the average value of 43.97% an increase of 61.8%. If compared with the average value of the berfore siklus 36.53% to the average obtained in the second cycle of 71.15%, it is known to increase the ability of the introduction of the concept of color children of 94.7%. Thus playing dominoes color can enhance the ability of the introduction of color in children aged 4-5 years in the planning. Bunga Teratai Tapung accordance with the desired expectations in this study. This increase occurred due to the implementation of each stage in the cycle to improve learning activities.Key words: Introduction Concepts, Play Cards On Domino Colours